ANALISIS PENGARUH STOCK SPLIT TERHADAP HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM ( Studi Pada Perusahaan Yang Terdaftar Di BEI 2014-2017) - Ahmad Zeky Sandra; Mohammad Amin; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThis study aims to find out the differences in Stock Split Effect on StockPrices and Stock Trading Volume. The data used in this study are secondary data,the study population is a company listed on the Indonesia Stock Exchange whilethe research sample taken from a company that conducts a stock split. Thesampling technique was carried out using purposive sampling method. The resultsobtained using the Kolmogorov-Smirnov test for the stock price before (0.012 50.05) and after Stock Split (0.016 ≤ 005) for trading volume of shares 0.001 ≤0.05, and the test of this study using Wilcoxon Test Signed Ranks Test for stockprices 0.041 5 0.05 and stock trading volume 0.049 5 0.05. The results of thisstudy indicate that there are differences in stock prices and trading volume beforeand after the stock split.Keywords: Stock Split, Price, Volume